'Wasted precariat': Migrant work in European societies. (April 2016) - Pajnik, Mojca
This article discusses migrants' experiences of European migration-labour. It shows how precariousness is materialized in migrants' work and lives. I show how the subordination of migrants to the demands of the (global) market shapes the work of 'third country migrants' as precarious in European economies. Specific migration policies as well as labour processes and their regulation construct migrants as 'wasted precariat', in line with Bauman's (2004) notion of 'wasted humans'. This process occurs at the intersection of migrant workers' immigration status, the governance of immigration and labour relations as well as features of the industries that employ migrant workers.